Focus on markets and marketing - Coate, Patricia (Business strategy series, 2007)
This e-book contains a series of articles on marketing and the latest innovative methods that companies are using to reach new markets, specifically geographical new markets, such as China and Japan. This e-book includes contributions from authors from Deloitte, and Lippincott Mercer.